Star wars: age of republic ebook - Guggenheim, Marc (Star Wars: Age Of Republic (2018)., 2020)
Collects Star Wars: Age of Republic - Anakin Skywalker #1, Star Wars: Age of Republic - Count Dooku #1, Star Wars: Age of Republic - Darth Maul #1, Star Wars: Age of Republic - General Grievous #1, Star Wars: Age of Republic - Jango Fett #1, Star Wars: Age of Republic - Obi-Wan Kenobi #1, Star Wars: Age of Republic - Padme Amidala #1, Star Wars: Age of Republic - Qui-Gon Jinn #1, Star Wars: Age of Republic Special #1. Beginning the Age of Star Wars — epic adventures featuring your favorite characters from all three film trilogies! And first up are the heroes and villains of the days of the Old Republic! Witness the moments that define them, the incredible battles that shaped them — and their eternal conflict between light and darkness! Solo stories spotlight major figures from Star Wars Episodes I-III — including Qui-Gon Jinn, Obi-Wan Kenobi, Anakin Skywalker, Mace Windu…and Jar Jar Binks! And don't forget those who lurk on the dark side — fearsome foes like Count Dooku, Darth Maul, Jango Fett and more!